ANALISIS STRATEGI PENINGKATAN KAPASITAS OPERASIONAL PELABUHAN PERIKANAN PANTAI ERETAN WETAN KABUPATEN INDRAMAYU - Putri, Rasti Eka; Rosyid, Abdul; Boesono, Herry (Journal of Fisheries Resources Utilization Management and Technology, 2013)
The development pattern of Eretan Wetan Coastal Fishery Port needs to be adjust to the development of fishery activities. The aims of this research are to analyze operational level PPP Eretan Wetan and analyze the level of utilization of basic and functional facilities. As soon as formulating to strategies building the operational capacity of PPP Eretan Wetan. The used method is by using the descriptive survey method with case study. Data are collected through observation, interviews, documentation and collected data from PPP Eretan Wetan. Data collection process is limited only in the periode of 2007 – 2011. SWOT analysis is used to determine the operational capacity. From the research result, it can be found that the level operational and utilization rate of facilities in PPP Eretan Wetan not all used optimally, can be seen from the use of the pier, which is 12,5% and 27% auction house. Strategy to increase the operational capacity of P PP Eretan Wetan is: continue the development of PPP aggressively, quickly add basic amenities, functional and support that has not been met, groove cruise facilities should frequently in dredging due to silting, providing docking facilities and ice plants; addition of fleet fishing vessels, so that fish production can be optimized, increasing the quality of human resources through training and empowerment of fishermen and baskets, Developing cooperation with the fish processing industry; additional support facilities and improved quality of fish marketing facilities to support the marketing of fish, and increase the number of environmentally friendly fishing gear that accordance with the target economically important fisheries.